Technological Capabilities of Vacuum Arc Plasma Sources. (October 2014) - Bystrov, Yu. A.; Vetrov, N. Z.; Lisenkov, A. A.; Kostrin, D. K.
Abstract Vacuum arc plasma sources based on the self‐maintained discharge developing in the cathode material vapor enable plasmochemical synthesis of nitride and carbide compounds. Reactive gas is injected in the metal plasma flux to implement the plasmochemical synthesis of compounds. By controlling the plasma flux parameters and taking into account the ion current density distribution in the active volume, properties of the formed coating may be managed. The development of plasma technology leads to possibility of fine controlling of gas pressure and reactive gas composition, degree of plasma flux focusing, flux separation from the drop fraction. If the plasma flux is free of droplets the composition and structure of a coating can be effectively controlled by varying technological parameters.